2010
DOI: 10.1093/nar/gkp1075
|View full text |Cite
|
Sign up to set email alerts
|

RNA helicase A modulates translation of HIV-1 and infectivity of progeny virions

Abstract: Retroviruses rely on host RNA-binding proteins to modulate various steps in their replication. Previously several animal retroviruses were determined to mediate Dhx9/RNA helicase A (RHA) interaction with a 5′ terminal post-transcriptional control element (PCE) for efficient translation. Herein PCE reporter assays determined HTLV-1 and HIV-1 RU5 confer orientation-dependent PCE activity. The effect of Dhx9/RHA down-regulation and rescue with siRNA-resistant RHA on expression of HIV-1NL4–3 provirus determined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
143
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(149 citation statements)
references
References 36 publications
6
143
0
Order By: Relevance
“…Conversely, mutations of its conserved lysine residues eliminated interaction with PCE RNA in cells and did not block translation of PCE RNA. Our results indicate that N-term basic residues of RHA are necessary to engage the RNA structure and to deliver the ATP-dependent helicase activity that is necessary for translation of PCE mRNA (3). This N-term interaction is selective for functional PCE because the binding affinity for nonfunctional PCE (mutAC) is reduced by a factor of 2-3, and binding to negative control dsRNAs is not detectable.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Conversely, mutations of its conserved lysine residues eliminated interaction with PCE RNA in cells and did not block translation of PCE RNA. Our results indicate that N-term basic residues of RHA are necessary to engage the RNA structure and to deliver the ATP-dependent helicase activity that is necessary for translation of PCE mRNA (3). This N-term interaction is selective for functional PCE because the binding affinity for nonfunctional PCE (mutAC) is reduced by a factor of 2-3, and binding to negative control dsRNAs is not detectable.…”
Section: Discussionmentioning
confidence: 87%
“…PCE activity is attributable to two functionally redundant stem-loop structures (A and C) (2,21). Mutations that disrupt structural features of structures A and C (referred to as mutAC) in spleen necrosis virus (SNV), an avian retrovirus, eliminate translation activity and detectable interaction with epitope-tagged RHA (FLAG-RHA) in cells, whereas compensatory mutations restore translation activity and interaction with FLAG-RHA (1)(2)(3)24). These observations provide a framework to determine the residues of RHA necessary for functionally relevant interaction with PCE.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…55,[58][59][60] In this process, these enzymes are delivered to the 5 0 end of the mRNA either by binding to a specific post-transcriptional element (PCE) in the case of RHA, as part of the eIF4F complex for Ded1, or together with the 40S ribosomal subunit for DHX29. [60][61][62] In the case of HIV-1, BorisLawrie and colleagues have addressed the role of DHX9/RHA in viral translation and they showed that the latter was required to promote RNP remodeling through the 5 0 UTR to ensure ribosome progression. 61 This occurs by the initial binding of RHA to the PCE element found in the HIV-1 5…”
Section: The Need For Additional Helicases In Hiv-1 Translationmentioning
confidence: 99%